The truth, the whole truth, and nothing but the truth a multiple country test of an oath script - Frederik Carlsson; Mitesh Kataria; Alan Krupnick; Elina Lampi; Asa Löfgren (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
Hypothetical bias is one of the main issues bedeviling the field of nonmarket valuation. The general criticism is that survey responses reflect how people would like to behave, rather than how they actually behave. In our study of climate change and emissions reductions, we took advantage of the increasing bulk of evidence from psychology and economics that addresses the effects of making promises, in order to investigate the effect of an oath script in a contingent valuation survey. The survey was conducted in Sweden and China, and its results indicate that an oath script has significant effects on respondent behavior in answering willingness-to-pay (WTP) questions, some of which vary by country. In both countries, the share of zero WTP responses and extremely high WTP responses decreases when an oath script is used, which also results in lower variance. In China, the oath script also reduces the average WTP, cutting it by half in certain instances. We also found that the oath script has different impacts on various respondent groups. For example, without the oath script, Communist party members in China are more likely than others to have a positive WTP for emissions reductions, but with the oath script, there is no longer any difference between the groups.
Keywords: D61; Q5; 330; oath script; hypothetical bias; willingness to pay; Willingness to pay; Klimaschutz; Bias; Psychologie; Test; China; Schweden